Diagnostic accuracy of shear wave elastography in evaluating renal fibrosis in children with chronic kidney disease: a comparative study with Tc-99 DMSA renal scan - Aya Abdelgawad; Randa Abdallah; Nora Nabil (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Chronic kidney disease (CKD) is a global public health issue, impacting over 10% of the world’s population, amounting to more than 800 million individuals. However, the true number of people affected by CKD could be much higher due to increasing risk factors like obesity, hypertension, and diabetes. CKD is a progressive condition leading to tubular atrophy and interstitial fibrosis, encompasses a variety of diseases that impair the structure and function of the kidneys. Aim To evaluate the accuracy of shear wave elastography to detect renal parenchymal fibrosis in children with chronic kidney disease in comparison with technetium-99 m dimercaptosuccinic acid (DMSA) scan. Methods A case–control study. Cases were pediatric patients with CKD who referred for DMSA scan from the pediatric hospital while the controls are recruited from the pediatric outpatient clinics referred for an abdominal ultrasound for reasons other than renal pathology at the radiology department of our institution. Both cases and control group underwent ultrasound examination with shear wave elastography. Results The average elasticity values from 20 controls taken in our study were 11.02(9.58–11.5) kpa. In our study shear wave elastography (SWE) could predict scar on DMSA at a cutoff elasticity value of ≥ 12.065 kpa with a sensitivity of 85.71 and specificity of 92.31. No significant difference in SWE values between controls and cases without scaring. Conclusions SWE is an affordable, widely available, and noninvasive technique with no radiation risk, making it valuable for monitoring disease progression and follow-up in children with CKD. Its high sensitivity and specificity in detecting renal scarring further enhance its clinical utility.